1937
DOI: 10.1158/ajc.1937.219
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Compounds as Carcinogenic Agents

Abstract: CHEMICAL RELATIONSHIPS Group I : Cholanthrene DerivativesThe carcinogenic compounds of the cholanthrene group merit separate consideration on account of their chemical relationship to the cholane (bile acid) class of naturally occurring substances. They are, however, of essentially the same type as the benzanthracene derivatives (see p. 222).Methylcholanthrene was prepared independently by Wieland and Dane (125) and by Cook and Haslewood (35) by dehydrogenation of dehydronorcholene, a pentacyclic hydrocarbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
2

Year Published

1937
1937
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(15 citation statements)
references
References 46 publications
1
12
0
2
Order By: Relevance
“…Repeated painting of mouse skin became the method of choice for demonstrating carcinogenic activity after the Kennaway group in England had used it to show that benzo(a)pyrene (BP) was the major carcinogen of coal tar (Cook et al, 1933). The isolation of BP was preceded and followed by the chemical synthesis of other carcinogenic PAHs (Cook et al, 1937;Kennaway and Hieger, 1930), some of which were later identified as minor components of coal tar.…”
Section: Introductionmentioning
confidence: 99%
“…Repeated painting of mouse skin became the method of choice for demonstrating carcinogenic activity after the Kennaway group in England had used it to show that benzo(a)pyrene (BP) was the major carcinogen of coal tar (Cook et al, 1933). The isolation of BP was preceded and followed by the chemical synthesis of other carcinogenic PAHs (Cook et al, 1937;Kennaway and Hieger, 1930), some of which were later identified as minor components of coal tar.…”
Section: Introductionmentioning
confidence: 99%
“…Bioassay-directed chemical characterization led to the identification of PAHs as cancer producing substances in coal tars (15), nitro PAHs as mutagenic substances in diesel emissions (12), and mutagenic hydroxylated nitro PAHs in ambient air (16). The first such studies (1,2) used animal tumor bioassays, however, the development ofshort-term genetic bioassays provided a more rapid method to identify mutagens and potential carcinogens in complex mixtures.…”
Section: Characterization Of Pommentioning
confidence: 99%
“…An embryologist might take the view that an inherited tendency, needing no extraneous influence, exists in the direction of squamous differentiation or that, if a stimulus is needed it may be supplied by some quantitative relationship of ovarian hormones, either excess or absence. The experimental pathologist, aware of the existence of naturally occurring carcinogens and of the suggestion that such substances are amenable to elaboration in animal tissues by comparatively simple chemical transformations (Cook, Haslewood, Hieger, Kennaway and Mayneord, 1937) or in virtue of their lipoid content (Hieger, 1949) might assume these to be the stimuli to squamous differentiation. The hypothetical natural stimuli would reach the mammary gland under the usual conditions of breeding in small amounts, presumably the same for all strains, over a long period of time and produce their effects at a late age in only 20 per cent of mice with this tendency.…”
Section: Incidence Of Lesionsmentioning
confidence: 99%